2013
DOI: 10.1111/dme.12059
|View full text |Cite
|
Sign up to set email alerts
|

Care of children with diabetes as inpatients: frequency of admissions, clinical care and patient experience

Abstract: There were a large number of admissions and the majority were emergencies. Parents generally felt that they receive good care, although with some lack of knowledge amongst the ward staff. There were an unacceptable number of adverse incidents reported. We recommend that education of ward staff in diabetes is carried out regularly with reference to the standards of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…A enfermagem deve constantemente avaliar a família submetida a seus cuidados (29)(30)(31)(32) , pois a comunicação positiva e otimista entre a família relaciona-se a melhores índices glicêmicos e de adesão ao tratamento por parte da criança (32) , implicando em melhor qualidade de vida, ao passo que conflitos familiares, altos níveis de hostilidade e críticas, sentimento de falta de ajuda dos pais pela criança levam a resultados opostos (32) .…”
Section: Discussionunclassified
“…A enfermagem deve constantemente avaliar a família submetida a seus cuidados (29)(30)(31)(32) , pois a comunicação positiva e otimista entre a família relaciona-se a melhores índices glicêmicos e de adesão ao tratamento por parte da criança (32) , implicando em melhor qualidade de vida, ao passo que conflitos familiares, altos níveis de hostilidade e críticas, sentimento de falta de ajuda dos pais pela criança levam a resultados opostos (32) .…”
Section: Discussionunclassified
“…Important elements are use of and adherence to policies, procedures, protocols, order sets, equipment, and therapeutic targets. 1,2,5,14,18–34 Several educational opportunities were identified, developed, and implemented by the ISC to improve knowledge of staff. Barbara Davis Center for Childhood Diabetes faculty, a certified diabetes educator, and clinical pharmacists developed education materials based on their expertise in insulin and diabetes management.…”
Section: Methodsmentioning
confidence: 99%
“…11–13 A recent study identified a large number of hypoglycemic events in children hospitalized for diabetes management and critical illness and called for increased staff education to prevent these adverse events. 14 …”
mentioning
confidence: 99%